Double checking: a second look. Issue 2 (16th November 2015) - Hewitt, Tanya; Chreim, Samia; Forster, Alan
Abstract: Rationale, aims and objectives: Double checking is a standard practice in many areas of health care, notwithstanding the lack of evidence supporting its efficacy. We ask in this study: 'How do front line practitioners conceptualize double checking? What are the weaknesses of double checking? What alternate views of double checking could render it a more robust process?' Method: This is part of a larger qualitative study based on 85 semi‐structured interviews of health care practitioners in general internal medicine and obstetrics and neonatology; thematic analysis of the transcribed interviews was undertaken. Inductive and deductive themes are reported. Results: Weaknesses in the double checking process include inconsistent conceptualization of double checking, double (or more) checking as a costly and time‐consuming procedure, double checking trusted as an accepted and stand‐alone process, and double checking as preventing reporting of near misses. Alternate views of double checking that would render it a more robust process include recognizing that double checking requires training and a dedicated environment, Introducing automated double checking, and expanding double checking beyond error detection. These results are linked with the concepts of collective efficiency thoroughness trade off (ETTO), an in‐family approach, and resilience. Conclusion(s): Double checking deserves more questioning, as there are limitations to the process. Practitioners could view double checking through alternate lenses, and thus help strengthen this ubiquitous practice that is rarely challenged.